The decline of the Ottoman Empire and the rise of the Turkish Republic: observations of an American Diplomat, 1919-1927 - Çolakoğlu, Emre Feyzi (ROUTLEDGE, 2021)
This book does little to advance our knowledge of these events because it is based on a limited reading of the relevant documents. The author only cites some of the Foreign Office records but the extensive cabinet, defence and treasury series which contain many vital files have been ignored. There are therefore significant gaps in this book, and the author has the tendency to make uncorroborated assertions. More significantly, this book contains a remarkable and shocking flaw. According to the bibliography, the author has employed a variety of State department records (called Record Group 59) at the US National Archives. None of the notes refer to their specific location or box numbers; the reader is only provided with ‘RG 59’. This is stunning error that should have been spotted by the publisher because other researchers will face an invidious challenge locating these records. The editing of this book is inadequate because the index is incomplete and even the knowledgeable reader is left confused by many incorrect references (some of the notes refer to FO 1017 or FCO 1016 whereas FO 1016 is correct), and some of them do not exist (such as FO 1056). One of the most significant limitations in writing about the modern history of the Persian Gulf is the dearth of accessible regional archives, which means that historians have to rely on the British documents.